Cryptosporidiosis outbreaks linked to the public water supply in a military camp, France. - Stéphanie Watier-Grillot; Damien Costa; Cédric Petit; Romy Razakandrainibe; Sébastien Larréché; Christelle Tong; Gwenaëlle Demont; David Billetorte; Damien Mouly; Didier Fontan; Guillaume Velut; Alexandra Le Corre; et al. (Public Library of Science (PLoS), 2022)
Introduction Contaminated drinking and recreational waters account for most of the reported Cryptosporidium spp. exposures in high-income countries. In June 2017, two successive cryptosporidiosis outbreaks occurred among service members in a military training camp located in Southwest France. Several other gastroenteritis outbreaks were previously reported in this camp, all among trainees in the days following their arrival, without any causative pathogen identification. Epidemiological, microbiological and environmental investigations were carried out to explain theses outbreaks. Material and methods Syndromic diagnosis using multiplex PCR was used for stool testing. Water samples (100 L) were collected at 10 points of the drinking water installations and enumeration of Cryptosporidium oocysts performed. The identification of Cryptosporidium species was performed using real-time 18S SSU rRNA PCR and confirmed by GP60 sequencing. Results A total of 100 human cases were reported with a global attack rate of 27.8%. Cryptosporidium spp. was identified in 93% of stool samples with syndromic multiplex PCR. The entire drinking water network was contaminated with Cryptosporidium spp. The highest level of contamination was found in groundwater and in the water leaving the treatment plant, with >1,000 oocysts per 100 L. The same Cryptosporidium hominis isolate subtype IbA10G2 was identified in patients' stool and water samples. Several polluting activities were identified within the protection perimeters of the water resource. An additional ultrafiltration module was installed at the outlet of the water treatment plant. After several weeks, no Cryptosporidium oocysts were found in the public water supply. Conclusions After successive and unexplained gastroenteritis outbreaks, this investigation confirmed a waterborne outbreak due to Cryptosporidium hominis subtype IbA10G2. Our study demonstrates the value of syndromic diagnosis for gastroenteritis outbreak investigation. Our results also highlight the importance of better assessing the microbiological risk associated with raw water and the need for sensitive and easy-to-implement tools for parasite detection.